Effects of Miltefosine and Other Alkylphosphocholines on Human Intestinal Parasite Entamoeba histolytica - Seifert, Karin (American Society for Microbiology, 2001)
The protozoan parasite Entamoeba histolytica is the cause of amoebic dysentery and liver abscess. It is therefore responsible for significant morbidity and mortality in a number of countries. Infections with E. histolytica are treated with nitroimidazoles, primarily with metronidazole. At this time, there is a lack of useful alternative classes of substances for the treatment of invasive amoebiasis. Alkylphosphocholines (alkyl-PCs) such as hexadecyl-PC (miltefosine) were originally developed as antitumor agents, but recently they have been successfully used for the treatment of visceral leishmaniasis in humans. We examined hexadecyl-PC and several other alkyl-PCs with longer alkyl chains, with and without double bond(s), for their activity against two strains of E. histolytica. The compounds with the highest activity were oleyl-PC, octadecyl-PC, and nonadecenyl-PC, with 50% effective concentrations for 48 h of treatment between 15 and 21 μM for strain SFL-3 and between 73 and 98 μM for strain HM-1:IMSS. We also tested liposomal formulations of these alkyl-PCs and miltefosine. The alkyl-PC liposomes showed slightly lower activity, but are expected to be well tolerated. Liposomal formulations of oleyl-PC or closely related alkyl-PCs could be promising candidates for testing as broad-spectrum antiprotozoal and antitumor agents in humans.